Investigating vaterite phase stabilisation by a tetrazole molecule during calcium carbonate crystallisation - Massi, Max; Ogden, Mark; Jones, Franca (Elsevier Science BV, 2012)
Tetrazole compounds have recently been found to impact on crystal morphology but in a manner different from that of carboxylate molecules. One such molecule was found to stabilise vaterite and this was investigated by assessing the impact of systematic changes on its structure. It was found that both the tetrazole and the formyl functionalities were required for vaterite stabilisation. The mechanism of stabilisation appears to be via inhibition of vaterite dissolution.